Incident Cheyne-Stokes respiration occurring in CPAP-treated patients and cardiovascular risk: a 2-years prospective follow-up (The Alertapnee study) - Arnaud Prigent; Joëlle Texereau; Sébastien Bailly; Renaud Gervais; Anne-Laure Serandour; Régis Luraine; Jean Louis Pépin (Respiratory Research)
Abstract The Alertapnée study followed 555 adults with obstructive sleep apnea treated with CPAP and found that the occurrence of Cheyne-Stokes respiration (CSR) was linked to a 14-fold increase in the risk of significant cardiac events (SCE) after one year. However, the progression and clinical significance of CSR episodes over time remain unclear. This ancillary study aimed to assess CSR progression and clinical outcomes during a second year of follow-up in 66 patients who had experienced at least one CSR episode in the first year. The study focused on the number of nights with CSR, percentage of CSR, SCEs. Results showed that 62 of 66 patients with CSR in the first year also experienced CSR in the second year, with a significant increase in the median number of CSR nights, particularly when CSR was related to cardiovascular conditions (37 vs. 19 nights, p = 0.006). Patients who experienced a SCE in year 2 had significantly more nights with CSR (median 48/90nights; IQR = 35) and a significantly greater mean percentage of CSR (median 13.8%; interquartile range (IQR) = 13.7) as compared with patients free of SCE (median 9.5/90 nights IQR = 27.8 (p = 0.012); 6.1% IQR = 4.5 (p = 0.008), respectively). In conclusion, CSR occurrence and severity depend on the underlying condition. CSR related to cardiovascular aetiology increases over time and is associated with SCEs, whereas CSR linked to non-cardiovascular conditions does not indicate a poor prognosis. Identifying CSR patterns related to cardiovascular aetiologies could enable early detection of SCEs through telemonitoring in CPAP-treated patients.